Great hammerhead sharks swim on their side to reduce transport costs - Payne, N. L.; Iosilevskii, G.; Barnett, A.; Fischer, C.; Graham, R. T.; Gleiss, A. C.; Watanabe, Y. Y. (The Journal of Experimental Biology, 2016)
Breaststroke, butterfly, front crawl and back crawl: many of us learnt these swimming styles as kids while splashing around in our local pool. These strokes all involve the swimmer lying on their back or front, much like the way most fish swim. Of course, some people prefer to swim tilted to one side rather than face down even though the side-stroke evokes images of elderly swimmers in bathing caps rather than speed and athletic prowess. However, a new study from a team of international researchers suggests that your grandparents` side-tilted swimming style may have something in common with a rather different type of sea creature: the great hammerhead shark.